Progress in Gene Editing Tools and Their Potential for Correcting Mutations Underlying Hearing and Vision Loss - Botto, Catherine; Dalkara, Deniz; El-Amraoui, Aziz (Frontiers in Genome Editing, 2021)
Blindness and deafness are the most frequent sensory disorders in humans. Whatever its origin — genetic, environmental, or due to toxic agents, or aging — the deterioration of these senses is often linked to irreversible damage to the light-sensing cells (blindness) and/or the mechanosensitive sensory cells (deafness). Efforts are increasingly focusing on preventing disease progression by correcting or replacing pathogenic alleles. In recent years, gene replacement therapies for rare monogenic disorders of the retina have given positive results, leading to the marketing of the first gene therapy product for a form of childhood hereditary blindness. Promising results, with a partial restoration of auditory function, have also been reported in preclinical models of human deafness. Silencing approaches, including antisense oligonucleotides, adeno-associated virus (AAV)–mediated microRNA delivery, and genome-editing approaches have also been applied to various genetic forms of blindness and deafness. The advent of new editing agents, for base and prime editing, for example, offers new possibilities for directly repairing point mutations and therapeutically restoring gene function, particularly in non-dividing cells. The eye and inner ear will continue to be key targets in the development of therapeutic applications of CRISPR for gene editing. Here, we review the ongoing applications of this new class of emerging therapeutics in the sensory organs of vision and hearing, highlighting the challenges ahead and the solutions to be overcome for their application in vivo.